PENGARUH PROFITABILITAS, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR CONSUMER CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Puspa Koesrawaty; A. Syahrul Makkuradde; Anugrah Lutfi; Mattarima Mattarima; Izaac Lawalata (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2023)
Company value is the perception of investors and shareholders on the company's success rate which is often associated with the stock price. Because by maximizing the value of the company, it is agreed as the goal of every profit-oriented company and by increasing the value of the company means the same as maximizing the company's stock price. One of the factors that affect the value of the company is the ups and downs of profitability obtained by the company because profitability is believed to be able to determine the value of the company. Profitability is one of the most important ratios for investors when making investment decisions, this profitability ratio can describe a company's ability to use its resources to generate profits over a period of time. The purpose of this study is to determine the effect of profitability, liquidity, company size on company value in the consumer cyclicals sector listed on the Indonesia Stock Exchange. The analytical method used in this study is quantitative descriptive analysis using Multiple Linear Regression data analysis with a population of 41 companies and the number of samples used as many as 10 companies. The results of this research analysis show that profitability has a positive and significant effect on company value, while liquidity and company size have a negative and insignificant effect on company value in the consumer cyclicals sector listed on the Indonesia Stock Exchange